Electronic pathway in reaction centers from Rhodobacter sphaeroides and Chloroflexus aurantiacus - Pudlak, Michal (Springer Netherlands, 2010)
The reaction centers (RC) of Chloroflexus aurantiacus and Rhodobacter sphaeroidesH(M182)L mutant were investigated. Prediction for electron transfer (ET) at very low temperatures was also performed. To describe the kinetics of the C. aurantiacus RCs, the incoherent model of electron transfer was used. It was shown that the asymmetry in electronic coupling parameters must be included to explain the experiments. For the description of R. sphaeroidesH(M182)L mutant RCs, the coherent and incoherent models of electron transfer were used. These two models are discussed with regard to the observed electron transfer kinetics. It seems likely that the electron transfer asymmetry in R. sphaeroides RCs is caused mainly by the asymmetry in the free energy levels of L- and M-side cofactors. In the case of C. aurantiacus RCs, the unidirectionality of the charge separation can be caused mainly by the difference in the electronic coupling parameters in two branches.